Dynamic Raman spectroscopy of hydrogen isotopomer mixtures in-line at TILO - Helmut Telle (Laser Physics Letters, 2008)
The pure rotational and vibration-rotational Stokes Raman spectra of flowing gaseous mixtures of the hydrogen isotopomers H2, HD, and D2 were measured in order to test the performance of the proposed tritium purity monitoring system designed for the Karlsruhe Tritium Neutrino (KATRIN) mass experiment, which utilises 532 nm CW laser excitation and fibrecoupled scattered light collection, exploiting 90° excitation observation geometry. Short (100–300 s) exposure times were used to simulate the real-time in-line measurement of hydrogen isotopomer composition at the low (∼ 100–150 mbar) pressure required for KATRIN. At 100 s exposure time, an in-line sensitivity of better than 1% was achieved for dynamic changes in the sample gas composition.